Development of Pollen-free Easter Lily strains by Cross-breeding Lilium × formolongi hort. and Easter Lily (Lilium longiflorum Thunb.) - Okazaki, Keiichi; Yokoi, Naoto; Imakiire, Seiro; Saito, Takaaki (Engeigaku kenkyuu, 2023)
A pollen-free strain was obtained in the F2 generation by cross-breeding of Lilium × formolongi variety ‘Akita Kiyohime’ and Easter lily (Lilium longiflorum) variety. The gene for pollen-free is recessive inheritance. The incidence of pollen-free individuals in the F2 generation is influenced by seed germination rate, bolting rate, and flowering rate of the strain, and fluctuates. The cultivated strain shows vigorous growth of Lilium × formolongi in addition to being completely pollen-free, and can produce cut flowers with smaller bulbs than the conventional Easter lily variety.